Highly efficient (R-X-R)-type carbamates as molecular transporters for cellular delivery - Patil, Kiran M.; Naik, Rangeetha J.; Rajpal; Fernandes, Moneesha; Ganguli, Munia; Kumar, Vaijayanti A. (Journal of the American Chemical Society, 2012)
The (R-X-R) motif-containing arginine-rich peptides are among the most effective cell-penetrating peptides. The replacement of amide linkages in the (R-X-R) motif by carbamate linkages as in (r-ahx-r)(4) or (r-ahx-r-r-apr-r)(2) increases the efficacy of such oligomers several-fold. Internalization of these oligomers in mammalian cell lines occurs by an energy-independent process. These oligomers show efficient delivery of biologically active plasmid DNA into CHO-K1 cells.